MODERN APPROACHES TO RAW MATERIAL INVENTORY MANAGEMENT IN GLOBAL SUPPLY CHAINS (International journal of artificial intelligence, 2026)
This article examines modern theoretical and practical approaches to raw material inventory management in the context of digital transformation, resilient supply chains, and sustainable industrial development. The research focuses on recent methodological changes in inventory formation, planning, and distribution systems between 2021 and 2026. Special attention is given to Demand-Driven Material Requirements Planning (DDMRP), AI-driven forecasting, digital twins, and resilient sourcing models. The article also analyzes current industrial and logistics trends in Uzbekistan and evaluates opportunities for implementing smart inventory systems in manufacturing enterprises. The findings indicate that data-driven inventory management and digital integration significantly improve operational efficiency, reduce costs, and increase supply chain resilience.